2022
DOI: 10.1097/cin.0000000000000939
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Patient Education Multimodal Digital Platform on Knowledge Acquisition, Self-efficacy, and Patient Satisfaction

Abstract: This study examined the impact of digital training instrument based on multimodal learning approach on surgical ward hospitalized patient education–related variables. The study was conducted as a multisite study in a large medical center as a two-arm, controlled trial with randomized cluster sampling. All patients meeting the inclusion criteria were offered the opportunity to participate. The control group (n = 40) received nurse explanation on home self-injection of enoxaparin sodium, whereas the intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…A multi‐site randomised control trial of 80 surgical patients found patients who received multiple learning modalities during admission, obtained significantly higher knowledge than patients who received written information only (Zhitomirsky & Aharony, 2022). Moreover, most PIP education includes giving information, shown to be the least effective way a patient comprehends information (Moore et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multi‐site randomised control trial of 80 surgical patients found patients who received multiple learning modalities during admission, obtained significantly higher knowledge than patients who received written information only (Zhitomirsky & Aharony, 2022). Moreover, most PIP education includes giving information, shown to be the least effective way a patient comprehends information (Moore et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A multi-site randomised control trial of 80 surgical patients found patients who received multiple learning modalities during admission, obtained significantly higher knowledge than patients who received written information only (Zhitomirsky & Aharony, 2022).…”
Section: Frequencymentioning
confidence: 99%
“…The flipped classroom is a multimodal approach that includes visual, auditory, reading, writing, and kinesthetic styles in the prescribed sequence of pre-work and skills-based activities [ [11] , [12] , [13] ]. Utilizing a multimodal approach improves learning experience and boost attention [ [14] , [15] , [16] ] and is shown to be effective in patient education programs [ 17 , 18 ]. The theoretical basis for the development of the flipped classroom is to elicit higher cognitive learning, according to the revised Bloom's taxonomy [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%